A hydrogen peroxide activatable nanoprobe for light-controlled "double-check" multi-colour fluorescence imaging. Issue 44 (23rd October 2020) - Zhang, Xing; Fu, Youxin; Liu, Jianping; Qian, Guangren; Zhang, Junji; Zhang, Run; Xu, Zhi Ping
Abstract : We report a photochromic molecule doped polymer nanoprobe in which the emission can be modulated by light and lysosomal hydrogen peroxide for multicolour fluorescence "double-check" imaging. Abstract : A new probe for precise and accurate bioimaging contributes significantly to advancing biomedical research for early disease diagnosis and treatment monitoring. Through wrapping a photochromic molecule (SP-Np-B) within a polymer nanoparticle, a new light-controlled multicolour fluorescence nanoprobe (Poly-SP-Np-B ) is developed for precise fluorescence subcellular bioimaging. Poly-SP-Np-B shows an "OFF–ON" red-emitting fluorescence response upon alternate UV/Vis light irradiation. After activation by hydrogen peroxide (H2 O2 ), a green-emitting Poly-SP-Np nanoparticle is generated, thus allowing light-controlled fluorescence response simultaneously, i.e., green and yellow switch upon alternate UV/Vis light irradiation for 10 and 20 s, respectively. Such a "blinking" fluorescence signal change is not possible by only using a photochromic molecule probe (SP-Np-B) with alternate UV/vis light irradiation for over 5 min. Poly-SP-Np-B has large isomerization kinetic constants ( k SP–MR = 0.4543 s −1 and k MR–SP = 0.0809 s −1 ), excellent biocompatibility and lysosome distribution capability, enabling multicolour fluorescence imaging in live cells. With exo-/endogenous H2 O2 activation in lysosomes, light-controlled "double-check" fluorescence imaging at the subcellular level is successfully achieved. More specifically, the change in fluorescence imaging is reversible in green, red and yellow channels in live cells upon excitation under alternate UV and visible light. This work thus provides a new strategy to develop switchable photochromic probes for precise fluorescence bioassay and bioimaging.